Service Design for the Public Sector - Lorenzo Imbesi; Birgit Mager; Luca D’Elia; Sonia Belhaj; Luca Baldini (DIID)
This contribution examines the application of Service Design within the public sector, drawing on the challenges posed by the so-called wicked problems to understand its potential and limitations. By critically reflecting on the unique constraints and complexities of government services and the differences with their commercial counterparts, the scope is to identify possible trajectories for future research and practice. While Service Design integrates multiple perspectives and works at different scales, responding to external and internal disturbances, it requires a comprehensive knowledge base that considers wicked problems’ properties such as demos, fragility and antifragility, degree of wickedness, public formation, plurality of values and approaches to Service Design for the public sector. Recognising these limitations and opportunities, the contribution invites a more nuanced understanding of Service Design in the public sector to decipher and address societal challenges.